An optimal analysis for magnetohydrodynamics Darcy‐Forchheimer boundary layer radiative flow past a porous medium. Issue 6 (29th December 2020) - Jawad, Muhammad; Saeed, Anwar; Shah, Zahir; Islam, Saeed; Kumam, Poom
Abstract: In this article, the study of magnetohydrodynamics Darcy‐Forchheimer flow is carried out. Viscous dissipation and thermal radiation are also deliberated for the flow system over a stretching and porous surface. Buongiorno model has been utilized to elaborate thermophoresis and Brownian dispersion impacts. The physical quantities such as viscosity, density, and specific heat play a key role in liquid flow behavior. The modeled equations are transformed to nonlinear ordinary differential equations and then solved by semi‐analytical technique HAM. It is found in this assessment that expanding estimations of the magnetic parameter builds Lorentz force and henceforth decreases the velocity profile. Moreover, velocity is also a reducing function of porosity and inertial parameters. The temperature of nanofluid diminishes with enhancement in the Prandtl number and porosity parameter while it increases with Brownian motion, radiation, thermophoretic parameters, and Brinkman number. The concentration profile is a growing function of the thermophoretic parameter and a reducing function of the Brownian motion parameter and Lewis number.